2013
DOI: 10.1111/j.1600-0706.2013.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of effective gene dispersal distances by pollen and seeds across successive life stages in a tropical tree

Abstract: Pollen and seed dispersal are the two key processes in which plant genes move in space, mostly mediated by animal dispersal vectors in tropical forests. Due to the movement patterns of pollinators and seed dispersers and subsequent complex spatial patterns in the mortality of offspring, we have little knowledge of how pollinators and seed dispersers affect effective gene dispersal distances across successive recruitment stages. Using six highly polymorphic microsatellite loci and parentage analyses, we quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 47 publications
4
12
1
Order By: Relevance
“…Usually, seed dispersal by frugivorous birds and large mammals should sustain gene flow across large distances, thereby leading to low levels of SGS. In fact, indirect estimations of gene dispersal distances (both pollen and seeds combined) from microsatellites revealed distances of 236-558 m. Further, also a direct assessment of contemporary pollen and seed dispersal distances using parentage analyses revealed seed dispersal distances of up to 700 m within our study population (Berens et al, 2013), with related individuals found even at far distances. However, direct estimates of pollen and seed dispersal revealed that the majority of seeds were dispersed across short distances, leading to a mean seed dispersal distance of only 5 m (Berens et al, 2013).…”
Section: Prevalence Of Sgs In P Africanamentioning
confidence: 84%
See 4 more Smart Citations
“…Usually, seed dispersal by frugivorous birds and large mammals should sustain gene flow across large distances, thereby leading to low levels of SGS. In fact, indirect estimations of gene dispersal distances (both pollen and seeds combined) from microsatellites revealed distances of 236-558 m. Further, also a direct assessment of contemporary pollen and seed dispersal distances using parentage analyses revealed seed dispersal distances of up to 700 m within our study population (Berens et al, 2013), with related individuals found even at far distances. However, direct estimates of pollen and seed dispersal revealed that the majority of seeds were dispersed across short distances, leading to a mean seed dispersal distance of only 5 m (Berens et al, 2013).…”
Section: Prevalence Of Sgs In P Africanamentioning
confidence: 84%
“…Our results suggested that seed dispersal was strongly distance restricted (mean distances of only 5 m), while pollen dispersal reached over 23-fold longer distances. Yet, strong nonrandom mortality led to a disproportionate increase of realized maternal gene flow distances at later life stages, as well as to strong variation in paternal gene flow distances (Berens et al, 2013). In this study, we used a multi-stage approach to determine whether the observed patterns of SGS are consistent with expectations deriving from the observed biological processes.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations